Conductive film for circuit boards, film for circuit boards, method for producing conductive film for circuit boards, method for producing film for circuit boards
Patent Information
- Application Number
- JP2022100487
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-03-28
- Filing Date
- 2022-06-22
- Publication Date
- 2025-03-05
- Estimated Expiration
- 2042-06-22
AI Technical Summary
【0019】 本発明によれば、基材と積層体(シード層)との密着性が優れ、回路基板用として好適に採用し得る回路基板用導電性フィルム、回路基板用フィルム、回路基板用導電性フィルムの製造方法、回路基板用フィルムの製造方法を提供することができる。
Smart Images

Figure 0007640097000006 
Figure 0007640097000007 
Figure 0007640097000008
Abstract
Description
[Technical field]
[0001] The present invention relates to a conductive film for circuit boards, a film for circuit boards, a method for producing a conductive film for circuit boards, and a method for producing a film for circuit boards. More specifically, the present invention relates to a conductive film for circuit boards, a film for circuit boards, a method for producing a conductive film for circuit boards, and a method for producing a film for circuit boards, which have excellent adhesion between a substrate and a laminate (seed layer) and can be suitably used for circuit boards. [Background technology]
[0002] Laminate substrates have been used in various fields in the past. Patent Document 1 discloses a laminate substrate that is made of a transparent base material and a laminate, the laminate having a blackened layer and a copper layer. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2017-49723 A Summary of the Invention [Problem to be solved by the invention]
[0004] However, the laminate substrate described in Patent Document 1 has poor adhesion between the transparent base material and the blackened layer, and therefore the conventional laminate substrate described in Patent Document 1 is unsuitable for use as a circuit board (e.g., FCCL, Flexible Copper Clad Laminate).
[0005] The present invention has been made in consideration of such conventional inventions, and aims to provide a conductive film for circuit boards, a film for circuit boards, a method for manufacturing a conductive film for circuit boards, and a method for manufacturing a film for circuit boards, which have excellent adhesion between a substrate and a laminate (seed layer) and can be suitably used for circuit boards. [Means for solving the problem]
[0006] As a result of intensive research, the present inventors have found that by configuring the seed layer of the laminate to contain copper, nickel, nitrogen, and oxygen and specifying the contents of oxygen and nitrogen, it is possible to improve the adhesion between the substrate and the seed layer, thereby solving the above-mentioned problems, and have completed the present invention. That is, the conductive film for circuit boards, the film for circuit boards, the method for producing the conductive film for circuit boards, and the method for producing the film for circuit boards of the present invention that solve the above-mentioned problems mainly include the following configurations.
[0007] (1) A conductive film for circuit boards, comprising: a substrate; and a laminate provided on at least one surface of the substrate, the laminate having, from the substrate side, a seed layer and a thin-film copper layer in this order, the seed layer containing copper, nickel, nitrogen, and oxygen, the seed layer having a nitrogen (N) content of 1.4 to 6.8 mass% calculated from the intensity of characteristic X-rays emitted in association with an outer-shell electron transition from the outer shell to the innermost K shell by EDX elemental analysis at an accelerating voltage of 10 kV, and an oxygen (O) content of 2.3 to 7.7 mass% calculated from the intensity of characteristic X-rays emitted in association with an outer-shell electron transition from the outer shell to the innermost K shell by EDX elemental analysis at an accelerating voltage of 10 kV.
[0008] According to such a configuration, the conductive film for circuit boards has excellent adhesion between the substrate and the laminate (seed layer), and therefore the conductive film for circuit boards can be suitably used for, for example, circuit boards.
[0009] (2) The conductive film for circuit boards according to (1), wherein the adhesion strength at the interface between the substrate and the seed layer is 0.7 N / mm or more.
[0010] According to such a configuration, the conductive film for circuit boards has better adhesion between the substrate and the laminate (seed layer), and therefore the conductive film for circuit boards can be more suitably used for, for example, circuit boards.
[0011] (3) The conductive film for circuit boards according to (1) or (2), wherein, in the L*a*b* color space, L* of reflected light at a wavelength of 300 to 800 nm when light is incident from the substrate side is 60 or less.
[0012] According to such a configuration, the conductive film for circuit boards can easily reduce the difference in visibility of reflected light between wiring portions and non-wiring portions, for example, when a patterned circuit board is produced using a light-transmitting substrate.
[0013] (4) A film for circuit boards, comprising the conductive film for circuit boards according to (1) or (2) above, and a plated copper layer provided on the thin-film copper layer.
[0014] With this configuration, the film for circuit boards tends to have a resistance value suitable for use on circuit boards.
[0015] (5) A method for producing a conductive film for circuit boards, comprising: a preparation step of preparing a substrate; and a laminate formation step of forming a laminate on at least one surface side of the substrate, the laminate having a seed layer and a thin-film copper layer in this order from the substrate side, the laminate formation step including a sputtering step of forming the seed layer by a sputtering method, the sputtering step being a step of forming the seed layer containing copper, nickel, nitrogen and oxygen by sputtering using a target of an alloy of copper and nickel and a mixed gas of nitrogen (N2) and oxygen (O2) as an introduction gas, and a ratio of a supply flow rate of nitrogen (N2) to a supply flow rate of oxygen (O2) in the supply flow rate of the mixed gas when the mixed gas is used as the introduction gas is 0.025≦(O2 / N2)≦0.4.
[0016] According to this configuration, the obtained conductive film for circuit boards has excellent adhesion between the substrate and the laminate (seed layer), and therefore the conductive film for circuit boards can be suitably used for, for example, circuit boards.
[0017] (6) A method for producing a film for circuit boards, comprising: obtaining a conductive film for circuit boards by the method for producing a conductive film for circuit boards according to (5); and forming a plated copper layer on the thin-film copper layer of the conductive film for circuit boards by an electrolytic plating method.
[0018] According to this configuration, the obtained film for circuit boards tends to have a resistance value suitable for use on circuit boards. Effect of the Invention
[0019] According to the present invention, it is possible to provide a conductive film for circuit boards, a film for circuit boards, a manufacturing method for a conductive film for circuit boards, and a manufacturing method for a film for circuit boards, which have excellent adhesion between a substrate and a laminate (seed layer) and can be suitably used for circuit boards. [Brief description of the drawings]
[0020] [Figure 1] FIG. 1 is a schematic cross-sectional view of a conductive film for circuit boards according to one embodiment of the present invention. [Diagram 2] FIG. 2 is a schematic cross-sectional view of a film for circuit boards according to one embodiment of the present invention. [Diagram 3] FIG. 3 is a graph in which the horizontal axis represents O2 / N2, which is the ratio of the supply flow rates (sccm) of nitrogen (N2) and oxygen (O2) used as the introduced gases, and the vertical axis represents the adhesion strength at the interface between the substrate and the seed layer. [Figure 4] FIG. 4 is a graph showing the results of determining the O2 / N2 ratio from an approximation curve when the adhesion is in the preferred range of 1.0 N / mm or more and 0.7 N / mm or more. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0021] <Conductive film for circuit boards> FIG. 1 is a schematic cross-sectional view of a conductive film for circuit boards (hereinafter, simply referred to as conductive film 1) according to one embodiment of the present invention. The conductive film 1 of this embodiment includes a substrate 2 and a laminate 3 provided on at least one surface of the substrate 2. The laminate 3 includes a seed layer 4 and a thin-film copper layer 5, in this order, from the substrate 2 side. The seed layer 4 contains copper, nickel, nitrogen, and oxygen. The content of oxygen (O) in the seed layer 4 is calculated from the intensity of characteristic X-rays emitted in association with the outer-shell electron transition from the outer shell to the innermost K shell by EDX elemental analysis at an acceleration voltage of 10 kV, and is 2.3 to 7.7 mass %. The content of nitrogen (N) in the seed layer 4 is calculated from the intensity of characteristic X-rays emitted in association with the outer-shell electron transition from the outer shell to the innermost K shell by EDX elemental analysis at an acceleration voltage of 10 kV, and is 1.4 to 6.8 mass %. Each of these will be described below.
[0022] (Base material 2) The substrate 2 is not particularly limited. For example, the substrate 2 may be PI (polyimide), PET (polyethylene terephthalate), PEN (polyethylene naphthalate), PMMA (methacrylic resin), PP (polypropylene), PE (polyethylene), COP (cycloolefin polymer resin), PPS (polyphenylene sulfide resin), PS (polystyrene resin), fluororesin (e.g., PTFE, PFA, ETFE, FEP), PEEK (polyether ether ketone resin), etc. By using such a substrate 2, the film of the present embodiment is easy to handle and the productivity is easily increased.
[0023] The thickness of the substrate 2 is not particularly limited. For example, the thickness of the substrate 2 is preferably 6 μm or more, more preferably 12 μm or more, and even more preferably 25 μm or more. The thickness of the substrate 2 is preferably 300 μm or less, more preferably 250 μm or less, and even more preferably 200 μm or less. When the thickness of the substrate 2 is within the above range, the film has excellent handling properties and flexibility during processing. In addition, the film is easily suitable for use as a bendable circuit board. The average thickness of the substrate 2 can be appropriately adjusted depending on the use of the film. For example, in applications requiring a thinner film and high flexibility, the average thickness of the substrate 2 may be selected to be close to 6 μm. In addition, the average thickness of the substrate 2 may be selected to be close to 300 μm in terms of insulation, high reliability, and handling properties.
[0024] (Laminate 3) The laminate 3 is provided on at least one surface side of the base material 2. The laminate 3 has, from the base material 2 side, a seed layer 4 and a thin film copper layer 5 in this order.
[0025] Seed layer 4 The seed layer 4 is provided between the substrate 2 and the thin film copper layer 5. The seed layer 4 contains copper, nickel, nitrogen and oxygen.
[0026] In the alloy of copper and nickel, the copper content is preferably 32% by mass or more, more preferably 35% by mass or more, based on the total amount of copper and nickel in the seed layer 4. In addition, in the alloy of copper and nickel, the copper content is preferably 70% by mass or less, more preferably 56% by mass or less, even more preferably 45% by mass or less, and particularly preferably 40% by mass or less, based on the total amount of copper and nickel in the seed layer 4. By having the copper content within the above range, the alloy is no longer a ferromagnetic material at room temperature, and the magnetic permeability can be reduced. This makes it easier to form the alloy into a film by sputtering. In addition, the seed layer 4 is likely to have improved adhesion at the interface with the substrate 2, and excellent adhesion can be easily obtained.
[0027] On the other hand, in the alloy of copper and nickel, the content of nickel is preferably 30% by mass or more, more preferably 44% by mass or more, even more preferably 55% by mass or more, and particularly preferably 60% by mass or more, based on the total amount of copper and nickel in the seed layer 4. In addition, in the alloy of copper and nickel, the content of nickel is preferably 68% by mass or less, more preferably 65% by mass or less, based on the total amount of copper and nickel in the seed layer 4. By having the nickel content within the above range, the alloy is no longer a ferromagnetic material at room temperature, and the magnetic permeability can be reduced. This makes it easier to form the alloy into a film by sputtering. In addition, the seed layer 4 is likely to have improved adhesion at the interface with the substrate 2, and excellent adhesion can be easily obtained.
[0028] The content of oxygen (O) in the seed layer 4 may be 2.3 mass% or more, and preferably 2.6 mass% or more. The content of oxygen (O) in the seed layer 4 may be 7.7 mass% or less, and preferably 7.1 mass% or less. If the content of oxygen (O) is less than 2.3 mass%, the resulting conductive film 1 has poor adhesion between the substrate and the laminate (seed layer). On the other hand, if the content of oxygen (O) is more than 7.7 mass%, the resulting conductive film 1 has poor adhesion between the substrate and the laminate (seed layer).
[0029] The nitrogen (N) content in the seed layer 4 may be 1.4 mass% or more, and preferably 2.0 mass% or more. The nitrogen (N) content in the seed layer 4 may be 6.8 mass% or less, and preferably 6.5 mass% or less. If the nitrogen (N) content is less than 1.4 mass%, the resulting conductive film 1 has poor adhesion between the substrate and the laminate (seed layer). On the other hand, if the nitrogen (N) content exceeds 6.8 mass%, the resulting conductive film 1 has poor adhesion between the substrate and the laminate (seed layer).
[0030] In this embodiment, the copper content, nickel content, oxygen (O) content, and nitrogen (N) content are calculated from the characteristic X-ray intensity emitted in association with the outer shell electron transition from the outer shell to the innermost K shell by EDX elemental analysis at an acceleration voltage of 10 kV. Specifically, a sample (without the thin-film copper layer 5) in which a seed layer 4 is formed to a thickness of 60 nm on a Si wafer is subjected to an FE-SEM with an X-ray detector (FE-SEM: S4700 (manufactured by Hitachi, Ltd.), X-ray detector: EMAX 7200H (manufactured by Horiba, Ltd.)) at an acceleration voltage of 10 kV to measure the characteristic X-ray (K α1 +K α2 ) and for Ni and Cu, the intensity of the characteristic X-rays (K β1 +K β3 +K α1 +K α2 ) and the mass % can be calculated by using software installed in the X-ray detector (EMAX 7200H).
[0031] The total content of copper, nickel, nitrogen, and oxygen is preferably 90 mass % or more, more preferably 95 mass % or more, and even more preferably 98 mass % or more, based on the total amount of the seed layer 4. The seed layer 4 may contain other components as appropriate depending on the purpose, as long as the effects of this embodiment are achieved.
[0032] The adhesion at the interface between the substrate 2 and the seed layer 4 is preferably 0.7 N / mm or more, and more preferably 1.0 N / mm or more. When the adhesion is within the above range, the conductive film 1 has better adhesion between the substrate 2 and the laminate 3 (seed layer 4). Therefore, the conductive film 1 can be more suitably used for, for example, circuit boards. In this embodiment, the adhesion (adhesion strength) can be calculated by the following method. That is, the adhesion strength at the interface between the substrate 2 and the seed layer 4 can be measured by carrying out the following experiment.
[0033] <Adhesion strength> First, a seed layer and a thin copper layer are formed on a substrate in this order, then the surface of the thin copper layer is immersed in 5% by mass dilute sulfuric acid for 1 minute to clean the surface, then electroplating is performed at low current while stirring in copper sulfate aqueous solution by introducing air, and then electroplating is performed continuously at high current to obtain a plated copper layer with a total average thickness of 20 μm, and finally, the plated copper layer is immersed in 0.8% by mass benzotriazole solution for 5 minutes to perform rust prevention treatment, which is used as a test sample. Using the obtained test sample, the adhesion strength is measured based on the following measurement method. (Measurement method) A copper layer with an average thickness of 20 μm is formed on a 10 cm square thin-film copper layer sample by electrolytic plating, and then cut to a width of 5 mm. The sample is attached to a mount with double-sided adhesive tape. The base material part fixed to the mount is fixed to the lower clamp, and the seed layer and plated copper layer part that have been peeled off after a trigger are attached to the upper clamp. Using an autograph (Shimadzu Corporation), the sample is pulled at a speed of 50 mm / min and a tensile direction of 180°, and the load at that time is measured.
[0034] The thickness of the seed layer 4 is not particularly limited. For example, the thickness of the seed layer 4 is preferably 3 nm or more, more preferably 4 nm or more, and even more preferably 5 nm or more. The thickness of the seed layer 4 is preferably 100 nm or less, more preferably 50 nm or less, and even more preferably 25 nm or less. When the thickness of the seed layer 4 is within the above range, the conductive film 1 has excellent adhesion and excellent productivity.
[0035] Thin copper layer 5 The thin-film copper layer 5 is provided as a base for forming electrodes on a circuit board. Copper is inexpensive compared to other metals used in circuit boards and has a low resistivity, making it suitable as a metal species for forming a conductive pattern for a circuit board. Furthermore, by providing the thin-film copper layer 5, copper is easily deposited when a plated copper layer is subsequently formed. The thin-film copper layer 5, together with the above-mentioned seed layer 4, is etched into a desired pattern by a photolithography process when it is made into an FPC (Flexible Printed Circuit).
[0036] The thickness of the thin-film copper layer 5 is not particularly limited. For example, the thickness of the thin-film copper layer 5 is preferably 50 nm or more, more preferably 60 nm or more, and even more preferably 70 nm or more. When the thickness of the thin-film copper layer 5 is within the above range, the film is easily thickened by copper electrolytic plating. Moreover, the thickness of the thin-film copper layer 5 is preferably 5 μm or less, more preferably 3 μm or less, and even more preferably 2 μm or less. When the thickness of the thin-film copper layer 5 is within the above range, the conductive film 1 has excellent productivity.
[0037] Returning to the overall description of the conductive film 1, in the conductive film 1 of this embodiment, the laminate 3 is provided on at least one surface of the base material 2. The laminate 3 may be provided on both surfaces of the base material 2.
[0038] In the L*a*b* color space, the L* (brightness L* value) of the reflected light of the conductive film 1 at a wavelength of 300 to 800 nm when light is incident from the substrate side is preferably 60 or less, more preferably 50 or less. When L* is within the above range, the conductive film 1 is likely to suppress the difference in visibility of the reflected light between the wiring portion and the non-wiring portion, for example, when a patterned circuit board is produced using the light-transmitting substrate 2. In this embodiment, the "reflected light in the L*a*b* color space" can be measured by using, for example, an ultraviolet-visible-near-infrared spectrophotometer (UV-3600, manufactured by Shimadzu Corporation) under the conditions of a halogen lamp as the light source, integrating sphere light reception including regular reflection (geometric condition d(8°:di)), barium sulfate as the reference plate, and a wavelength range of 300 to 800 nm.
[0039] The conductive film 1 of this embodiment may have an anticorrosive layer (not shown) provided on the thin-film copper layer 5. The anticorrosive layer is preferentially oxidized (corroded) by oxygen in the air. Thus, the anticorrosive layer can prevent the thin-film copper layer 5 from being oxidized.
[0040] The anticorrosive layer preferably contains an alloy of copper and nickel. In the alloy of copper and nickel, the copper content is preferably 32 mass% or more, more preferably 35 mass% or more, based on the total amount of copper and nickel in the anticorrosive layer. In the alloy of copper and nickel, the copper content is preferably 70 mass% or less, more preferably 55 mass% or less, based on the total amount of copper and nickel in the anticorrosive layer. By having the copper content within the above range, the anticorrosive layer is easily prevented from oxidizing the thin-film copper layer 5, and is easily formed by sputtering.
[0041] On the other hand, in the copper-nickel alloy, the nickel content is preferably 30% by mass or more, more preferably 45% by mass or more, based on the total amount of copper and nickel in the anticorrosive layer. When the nickel content is within the above range, the antioxidation performance of the anticorrosive layer is more excellent, and an increase in the resistance value of the thin film copper layer 5 is suppressed. In addition, in the copper-nickel alloy, the nickel content is preferably 68% by mass or less, more preferably 65% by mass or less, based on the total amount of copper and nickel in the anticorrosive layer. When the nickel content is within the above range, the copper-nickel alloy loses its magnetic properties at room temperature, making it easier to form the anticorrosive layer by sputtering.
[0042] The content of the copper-nickel alloy is preferably 90% by mass or more, more preferably 95% by mass or more, and even more preferably 99% by mass or more, based on the total amount of the anticorrosive layer. The anticorrosive layer may contain other components as appropriate depending on the purpose, as long as the effects of this embodiment are achieved.
[0043] The method for forming the anticorrosive layer is not particularly limited. For example, the anticorrosive layer may be formed by a conventional physical vapor deposition method such as a sputtering method.
[0044] When an anticorrosive layer is provided, the thickness (average thickness) of the anticorrosive layer is preferably 1 nm or more, more preferably 3 nm or more. The thickness of the anticorrosive layer is preferably 9 nm or less, more preferably 7 nm or less. By having the thickness of the anticorrosive layer within the above range, oxidation of the thin film copper layer 5 is easily prevented.
[0045] In this embodiment, the seed layer, the thin-film copper layer, and the anti-rust layer have fine irregularities. Therefore, the thicknesses of the seed layer, the thin-film copper layer, and the anti-rust layer described above are average thicknesses. In this embodiment, the average thicknesses of the seed layer, the thin-film copper layer, and the anti-rust layer can be measured using a fluorescent X-ray measurement device. Specifically, first, a substrate on which a seed layer, a thin-film copper layer, and an anti-rust layer of a predetermined thickness are formed is prepared, and the physical film thicknesses of the seed layer, the thin-film copper layer, and the anti-rust layer of a predetermined thickness are measured using a contact step gauge. In addition, the amount of the seed layer, the thin-film copper layer, and the anti-rust layer in the seed layer, the thin-film copper layer, and the anti-rust layer of a predetermined thickness is measured by quantitative analysis using a fluorescent X-ray measurement device (XRF, ZSX Primus IV (scanning X-ray fluorescence analysis device), manufactured by Rigaku Corporation). A calibration curve is created from the film thickness measured by the contact step gauge and the amount of the seed layer material, the thin-film copper layer material, and the anti-rust layer material measured by quantitative analysis using XRF. The substrate on which the seed layer, thin-film copper layer, and anticorrosive layer are formed is subjected to quantitative analysis using XRF to detect nickel and copper (in the case of the seed layer and the anticorrosive layer), or copper (in the case of the thin-film copper layer) originating from the seed layer, thin-film copper layer, and anticorrosive layer, and the average value of the measured values at one to three points is taken as the average thickness. The average thickness of the seed layer, thin-film copper layer, and anticorrosive layer may be considered as the average value of the above-mentioned fine unevenness profile.
[0046] As described above, the conductive film 1 of the present embodiment has excellent adhesion between the substrate 2 and the laminate 3 (seed layer 4). Therefore, the conductive film for circuit boards can be suitably used for, for example, circuit boards.
[0047] <Method of manufacturing conductive film for circuit boards> A method for producing a conductive film for circuit boards according to one embodiment of the present invention (hereinafter, also referred to as a method for producing a conductive film) includes a preparation step of preparing a substrate, and a laminate formation step of forming a laminate having a seed layer and a thin-film copper layer in this order from the substrate side on at least one surface side of the substrate. The laminate formation step includes a sputtering step of forming a seed layer by a sputtering method. The sputtering step is a step of forming a seed layer containing copper, nickel, nitrogen, and oxygen by performing sputtering using a target of an alloy of copper and nickel and a mixed gas of nitrogen (N2) and oxygen (O2) as an introduction gas. When the mixed gas is used as the introduction gas, the ratio of the supply flow rate of nitrogen (N2) to the supply flow rate of oxygen (O2) in the supply flow rate of the mixed gas is 0.025≦(O2 / N2)≦0.4. Each of them will be described below. In the following description, the substrate and the laminate are the same as those described above in the embodiment of the conductive film.
[0048] Substrate preparation process and laminate formation process A laminate having a seed layer and a thin-film copper layer in this order from the substrate side is formed on at least one surface side of the prepared substrate.
[0049] The seed layer is laminated on the substrate by sputtering. The sputtering step is a step of forming a seed layer containing copper, nickel, nitrogen, and oxygen, in which the copper content is 35 to 70 mass% of the total of the copper content and the nickel content, by performing sputtering using a target of an alloy of copper and nickel and a mixed gas of nitrogen (N2) and oxygen (O2) as an introduction gas.
[0050] In the method for producing a conductive film according to the present embodiment, the nitrogen (N2) supply flow rate in the mixed gas supply flow rate when the mixed gas is used as the introduction gas is preferably 20 sccm or more, more preferably 40 sccm or more. The nitrogen (N2) supply flow rate is preferably 1000 sccm or less, more preferably 300 sccm or less. By setting the nitrogen (N2) supply flow rate within the above range, the obtained conductive film has an advantage of having a level of adhesion that is practically usable for circuit boards. In the present embodiment, "sccm" stands for Standard cubic centimeters per minute, and means a gas flow rate converted to a value at 1 atmosphere and 0°C.
[0051] In the method for producing a conductive film according to the present embodiment, when a mixed gas is used as the introduction gas, the supply flow rate of oxygen (O2) in the supply flow rate of the mixed gas is preferably 5 sccm or more, more preferably 10 sccm or more. The supply flow rate of oxygen (O2) is preferably 400 sccm or less, more preferably 120 sccm or less. By keeping the supply flow rate of oxygen (O2) within the above range, the obtained conductive film has a level of adhesion that allows practical use as a circuit board.
[0052] The method for producing a conductive film according to the present embodiment is characterized in that the ratio of the flow rate of nitrogen (N2) to the flow rate of oxygen (O2) in the supply flow rate of the mixed gas when the mixed gas is used as the introduction gas is adjusted to be 0.025≦(O2 / N2)≦0.4. The ratio (O2 / N2) may be 0.025 or more, and is preferably 0.03 or more. The ratio (O2 / N2) may be 0.4 or less, and is preferably 0.26 or less. When the ratio (O2 / N2) is less than 0.025, the obtained conductive film has poor adhesion between the substrate and the laminate (seed layer). On the other hand, when the ratio (O2 / N2) is more than 0.4, the obtained conductive film has poor adhesion between the substrate and the laminate (seed layer).
[0053] In the method for producing a conductive film of this embodiment, an inert gas (e.g., argon (Ar) or the like) may or may not be used. When an inert gas is not used, the method for producing a conductive film of this embodiment can reduce costs compared to using expensive argon (Ar) or the like.
[0054] The method of forming the thin-film copper layer on the seed layer is not particularly limited. For example, the thin-film copper layer can be formed by a conventionally known physical vapor deposition method such as a vacuum deposition method, a sputtering method, or an ion plating method. Among these, the conductive film of the present embodiment is preferably provided with a thin-film copper layer by a sputtering method because the film quality after deposition is excellent. The sputtering conditions can be appropriately selected from conventionally known conditions based on the desired thickness of the thin-film copper layer.
[0055] In addition, in the method for producing a conductive film according to the present embodiment, an anticorrosive layer may be formed on the thin copper layer. The method for forming the anticorrosive layer is not particularly limited. For example, the anticorrosive layer may be formed by a conventional physical vapor deposition method such as a sputtering method.
[0056] In addition, when an anticorrosive layer is formed, the anticorrosive layer is removed before the plated copper layer is formed. The process of removing the anticorrosive layer and the process of forming the plated copper layer will be described later in the method for producing a film for circuit boards.
[0057] As described above, according to the method for producing a conductive film of the present embodiment, the obtained conductive film for circuit boards has excellent adhesion between the substrate and the laminate (seed layer), and therefore the conductive film for circuit boards can be suitably used for, for example, circuit boards.
[0058] <Film for circuit boards> 2 is a schematic cross-sectional view of a film for circuit boards 6 according to one embodiment of the present invention. The film for circuit boards 6 of this embodiment includes the above-mentioned conductive film for circuit boards 1 and a plated copper layer 7 provided on the thin-film copper layer 5.
[0059] The plated copper layer 7 is a copper layer formed by electrolytic plating on the thin-film copper layer 5. When an anticorrosive layer is provided in the conductive film 1 described above, the plated copper layer 7 is provided on the exposed thin-film copper layer 5 after removing the anticorrosive layer. In the film for circuit boards 6 of the present embodiment, the plated copper layer 7 is formed on the thin-film copper layer 5 made of the same metal species as copper, so that copper is likely to accumulate when the plated copper layer 7 is formed.
[0060] The thickness of the plated copper layer 7 is not particularly limited. For example, the thickness of the plated copper layer 7 is preferably 1 μm or more, and more preferably 2 μm or more. The thickness of the plated copper layer 7 is preferably 50 μm or less, and more preferably 30 μm or less. When the thickness of the plated copper layer 7 is within the above range, the film for circuit boards 6 can achieve both low resistance and productivity.
[0061] As described above, the film for circuit boards 6 of this embodiment tends to have a resistance value suitable for use in circuit boards.
[0062] <Method of manufacturing film for circuit boards> A method for producing a film for circuit boards according to one embodiment of the present invention includes the steps of obtaining a conductive film for circuit boards by the above-mentioned method for producing a conductive film for circuit boards, and forming a plated copper layer on the thin copper layer of the conductive film for circuit boards by an electrolytic plating method. Note that the step of obtaining the conductive film for circuit boards and the plated copper layer that is formed are as described above in the embodiments of the method for producing a conductive film for circuit boards and the film for circuit boards.
[0063] The process of forming a plated copper layer The plated copper layer is formed on the thin copper layer by electrolytic plating. If the conductive film has an anticorrosive layer, the plated copper layer is formed after removing the anticorrosive layer. The method for removing the anticorrosive layer is not particularly limited. For example, the anticorrosive layer can be removed by washing with an acid such as dilute sulfuric acid, hydrogen peroxide, or ferric chloride.
[0064] In addition, the laminate may be subjected to a heat treatment before being washed with an acid in this manner. Even in such a case, the conductive film can prevent the thin-film copper layer from being oxidized because the conductive film has an anticorrosive layer.
[0065] After the anticorrosive layer is removed, a plated copper layer is formed on the exposed thin-film copper layer by electrolytic plating. The conditions of the electrolytic plating are not particularly limited. The electrolytic plating may employ a method using a copper sulfate bath, a copper cyanide bath, a copper pyrophosphate bath, or the like as an electrolytic bath. For example, the electrolytic plating may be performed by immersing a film in a copper sulfate bath and an electrode in a copper sulfate bath or the like, applying a voltage between the conductive film and the electrode, and causing a reduction reaction of copper ions in the copper sulfate bath on the thin-film copper layer.
[0066] By carrying out the above steps, the thin-film copper layer of the film for circuit board obtained is covered with the anticorrosive layer during the manufacturing process. This prevents oxidation of the thin-film copper layer even when the film for circuit board is heated before electrolytic plating is performed. In addition, the film for circuit board is sufficiently removed and the surface is cleaned before the plated copper layer is formed. Therefore, an increase in the resistance value of the thin-film copper layer is prevented. In addition, the plated copper layer is formed on the thin-film copper layer. At this time, since the plated copper layer is formed on the thin-film copper layer made of copper, which is the same metal species, it is easy to accumulate. In addition, the film for circuit board obtained is likely to have a resistance value suitable for use in a circuit board. EXAMPLES
[0067] The present invention will be described in more detail below with reference to the following examples. The present invention is not limited to these examples. Unless otherwise specified, "%" means "% by mass" and "parts" means "parts by mass".
[0068] <Example 1> A substrate (cycloolefin polymer (COP), ZF-16, manufactured by Zeon Corporation, thickness: 100 μm) was prepared. A copper-nickel alloy target (nickel 65 mass%, copper 35 mass%) was used for the substrate, and a mixed gas of nitrogen (N2) and oxygen (O2) was used as an introduction gas (nitrogen supply flow rate: 200 sccm, oxygen supply flow rate: 18 sccm) without using an inert gas, and a seed layer containing copper, nickel, nitrogen, and oxygen was formed by magnetron sputtering using a sputtering device so as to have a film thickness of 18 nm. Next, a thin-film copper layer was formed on the seed layer by magnetron sputtering using a sputtering device under Ar gas supply (Ar supply flow rate: 300 sccm) with a Cu target, so as to have a film thickness of 120 nm, to produce a conductive film for circuit boards.
[0069] <Examples 2 to 12, 18 to 22, Comparative Examples 1, 2, 9 to 11> A conductive film for circuit boards was produced in the same manner as in Example 1, except that the film formation conditions of the seed layer were adjusted according to the recipe shown in Table 1. In Table 1, "Ni-35Cu" indicates that a sputtering target of Ni-Cu alloy containing 35 mass% Cu (copper) and 65 mass% Ni (nickel) was used. "Ni-55Cu" indicates that a sputtering target of Ni-Cu alloy containing 55 mass% Cu (copper) and 45 mass% Ni (nickel) was used. "Ni-70Cu" indicates that a sputtering target of Ni-Cu alloy containing 70 mass% Cu (copper) and 30 mass% Ni (nickel) was used. The same applies to the descriptions in the other tables. In this case, the composition ratio of the Ni-Cu alloy in the seed layer formed using the Ni-35Cu target was analyzed by XPS, and it was confirmed that there was no substantial difference between the composition ratio of the target and the composition ratio of the film itself formed by sputtering. Thus, the composition ratio of the film and the composition ratio of the target can be regarded as being the same. Similarly, the composition ratio of the Ni-Cu alloy in the seed layer formed using the Ni-55Cu and Ni-70Cu targets can be regarded as being substantially the same as the composition ratio of the target and the composition ratio of the film itself formed by sputtering.
[0070] [Table 1]
[0071] The conductive films obtained in Examples 1 to 12, 18 to 22 and Comparative Examples 1, 2, and 9 to 11 were evaluated for "adhesion" according to the following method. The results are shown in Table 1 (the method for evaluating adhesion is the same for the other tables).
[0072] <Adhesion (adhesion strength)> First, for the conductive films obtained in Examples 1-12, 18-22 and Comparative Examples 1, 2, 9-11, the surface of the thin copper layer was immersed in 5% by mass diluted sulfuric acid for 1 minute to clean the surface, then electroplating was performed at low current while stirring in copper sulfate aqueous solution by introducing air, and then electroplating was performed continuously at high current to obtain a plated copper layer with a total average thickness of 20 μm, and finally, the plated copper layer was immersed in 0.8% by mass benzotriazole solution for 5 minutes to perform rust prevention treatment, which was used as a test sample. Using the obtained test sample, the adhesion strength was measured based on the following measurement method. (Measurement method) A copper layer with an average thickness of 20 μm was formed on a 10 cm square thin copper layer sample by electrolytic plating, and then cut to a width of 5 mm. The sample was attached to a mount with double-sided adhesive tape. The base material part fixed to the mount was fixed to the lower clamp, and the seed layer and plated copper layer part that were peeled off after a trigger were attached to the upper clamp. Using an autograph (Shimadzu Corporation), the sample was pulled at a speed of 50 mm / min and a tensile direction of 180°, and the load at that time was measured. As described above, the adhesion strength at the interface between the substrate and the seed layer was measured and evaluated according to the following evaluation criteria. (Adhesion Evaluation Criteria) -: The adhesion strength was too great to measure. ⊚: The adhesion strength was 1.0 N / mm or more. ◯: The adhesion strength was 0.7 N / mm or more and less than 1.0 N / mm. △: The adhesion strength was 0.5 N / mm or more and less than 0.7 N / mm. ×: The adhesion strength was less than 0.5 N / mm.
[0073] The reasons for adopting the above-mentioned criteria for evaluating adhesion are as follows. The reason for 1.0N / mm is that this is an excellent level for practical use on circuit boards. The reason why ◯ is 0.7 N / mm or more and less than 1.0 N / mm is that it is at a level that can be actually used for circuit boards. Reason for △ being 0.5 N / mm or more and less than 0.7 N / mm: This is because problems may arise in actual use for circuit boards. The reason why "x" is less than 0.5 N / mm: This is because there is a problem in practical use for circuit boards.
[0074] FIG. 3 is a graph plotting the adhesion at the interface between the substrate and the seed layer on the vertical axis against the O2 / N2 ratio, which is the ratio of the supply flow rate (sccm) of nitrogen (N2) and oxygen (O2) used as the introduced gas. In the horizontal axis of FIG. 3, when the O2 / N2 ratio is 0, it indicates that only N2 gas is introduced without introducing O2 gas, and when the O2 / N2 ratio is 1, it indicates that gas is introduced at a ratio of O2:N2=1:1. In addition, FIG. 3 also shows an approximation curve derived by plotting the above measured values. In this way, it was found that a range of high adhesion can be obtained by introducing a small amount of O2 under N2-rich conditions. In particular, the conductive film produced under the conditions of Example 1 showed a maximum adhesion value.
[0075] Next, elemental analysis of the seed layer of the conductive film of Example 1 was performed as follows using a technique called EDX (Energy Dispersive X-ray Spectroscopy). <Elemental analysis> The copper content, nickel content, oxygen (O) content, and nitrogen (N) content in the seed layer were calculated from the characteristic X-ray intensity emitted with the outer shell electron transition from the outer shell to the innermost K shell by EDX elemental analysis at an acceleration voltage of 10 kV. Specifically, a sample (without thin-film copper layer 5, Experimental Example 1) in which a seed layer 4 was formed to a thickness of 60 nm on a Si wafer was measured for the characteristic X-ray intensity emitted with the outer shell electron transition from the outer shell to the innermost K shell at an acceleration voltage of 10 kV using an FE-SEM with an X-ray detector (FE-SEM: S4700 (manufactured by Hitachi, Ltd.), X-ray detector: EMAX 7200H (manufactured by Horiba, Ltd.)). In Example 1, the seed layer had a thickness of 18 nm, but in Experimental Example 1, the seed layer had a thickness of 60 nm in order to perform elemental analysis more accurately. However, since the film formation conditions of the seed layer were the same as those of Example 1, it was considered that the amounts of various elements contained in the seed layer of Experimental Example 1 and Example 1 were the same. α1 +K α2 ) and for Ni and Cu, the intensity of the characteristic X-rays (K β1 +K β3 +K α1 +K α2 The intensity of the X-rays was measured, and the mass% was calculated using software installed in the X-ray detector (EMAX 7200H). The results are shown in Table 2.
[0076] [Table 2]
[0077] As can be seen from Table 2, it was confirmed that the composition ratio of Ni-35Cu (target) and the composition ratio of Ni and Cu in the seed layer formed were almost the same. For the following reasons, the sample of Experimental Example 1 was used with a different composition from the sample of Example 1. That is, if the sample of Example 1 is directly subjected to EDX elemental analysis, the influence of C (carbon) contained in the COP, which is the base material, is picked up significantly, and the correct composition ratio cannot be obtained. This is thought to be because the atomic numbers of C and N are adjacent to each other, and the intensities of the obtained characteristic X-rays interfere with each other. Therefore, in this experiment, in order to eliminate the influence of the base material, a Si wafer was used as the base material for measurement in Experimental Example 1. Under such circumstances, it was considered that the composition ratio this time (the composition ratio in the configuration of only the seed layer on the Si wafer) was the true composition ratio. In the following, the contents of N and O in the seed layer in Experimental Example 1 were regarded as the contents of N and O in the seed layer in Example 1.
[0078] Next, using the approximation curve of Figure 3, the O2 / N2 ratio at which the adhesion is in a preferable range and the N and O contents in the seed layer at that ratio were calculated from the N and O contents actually measured in Example 1 (Experimental Example 1).
[0079] Fig. 4 is a graph showing the results of finding the O2 / N2 ratio from an approximation curve when the adhesion is in the preferred range of 1.0 N / mm or more and 0.7 N / mm or more. As shown in Fig. 4, the adhesion is 0.7 N / mm or more when 0.025 < O2 / N2 ratio < 0.4. The adhesion is 1.0 N / mm or more when 0.03 < O2 / N2 ratio < 0.26. The adhesion is 0.5 N / mm or more when 0.02 < O2 / N2 ratio < 0.58.
[0080] The amounts of N and O contained in the seed layer were calculated by the following method when the O2 / N2 ratio reached the upper and lower limits of the above range. Here, the lower limit is the case where O decreased (N increased) from the contents of N and O actually measured in Example 1 (Experimental Example 1). On the other hand, the upper limit is the case where O increased (N decreased) from the contents of N and O actually measured in Example 1 (Experimental Example 1). <Calculation method> In Example 1 (Experimental Example 1), the value of (O / N) / (O2 / N2) is (5.0 / 4.1) / (18 / 200)=13.56...(Equation 1). Here, (O / N) is the ratio of the O and N contents in the seed layer, and (O2 / N2) is the ratio of the supply flow rates of O2 and N2, which are introduced gases during seed layer formation. From (Equation 1), (O / N) = (O2 / N2) x 13.56. For simplicity, (O2 / N2) = β. If the amount of decrease in O when O is decreased is α from the contents of O and N in Example 1 (Experimental Example 1), the content of O when O is decreased is (5.0-α), and the content of N when O is decreased is (4.1+α). Similarly, from the contents of O and N in Example 1 (Experimental Example 1), if the amount of increase in O when O is increased is α, the content of O when O is increased is (5.0+α), and the content of N when O is increased is (4.1-α). Therefore, when the O content is decreased from the O and N content in Example 1 (Experimental Example 1), (5.0-α) / (4.1+α)=13.56β. It is calculated as α = (5.0 - 55.596β) / (1 + 13.56β)... (Equation 2). On the other hand, when the content of O and N in Example 1 (Experimental Example 1) is increased, (5.0+α) / (4.1-α)=13.56β It is calculated as α = (55.596β - 5.0) / (1 + 13.56β)... (Equation 3).
[0081] From the above, the O2 / N2 ratio that provides a preferable range of adhesion of 1.0 N / mm or more, i.e., the value of α when the lower limit of β is 0.03, is α = 2.37 according to (Equation 2), and the O content at this time is (5.0 - α) = (5.0 - 2.37) = 2.63. Also, the N content at this time is (4.1 + α) = (4.1 + 2.37) = 6.47.
[0082] Using a similar procedure, the O2 / N2 ratio that provides a desirable range for adhesion of 1.0 N / mm or more, i.e., the value of α when the upper limit of β is 0.26, is calculated from (Equation 3) as α = 2.09, and the O content at this time is (5.0 + α) = (5.0 + 2.09) = 7.09. The N content at this time is (4.1 - α) = (4.1 - 2.09) = 2.01.
[0083] In the same manner as above, the O and N contents calculated from the upper and lower limits of other O2 / N2 ratios are shown in Table 3.
[0084] [Table 3]
[0085] In Table 3, the case where the O2 / N2 ratio was 0.03 was designated Example 1A, the case where the O2 / N2 ratio was 0.26 was designated Example 1B, the case where the O2 / N2 ratio was 0.025 was designated Example 1C, the case where the O2 / N2 ratio was 0.4 was designated Example 1D, the case where the O2 / N2 ratio was 0.02 was designated Comparative Example 1A, and the case where the O2 / N2 ratio was 0.58 was designated Comparative Example 1B. Therefore, the O and N contents for adhesion to be ◎ (≧1.0N / mm) are as follows: N: 2.0% by mass or more, 6.5% by mass or less O: 2.6% by mass or more, 7.1% by mass or less The O and N content for adhesion to be ○ (≧0.7N / mm or more) is: N: 1.4% by mass or more, 6.8% by mass or less O: 2.3% by mass or more, 7.7% by mass or less The O and N content at which the adhesion is △ (≧0.5N / mm or more) is: N: 1.0% by mass or more, 7.2% by mass or less O: 1.9% by mass or more, 8.1% by mass or less It was calculated that:
[0086] Next, the adhesion of Examples 1E, 1F, and 1G, which were produced in the same manner as in Example 1 except that the material and thickness of the substrate were changed from cycloolefin polymer (COP), were measured. The results are shown in Table 4.
[0087] [Table 4]
[0088] Table 4 shows that high adhesion was obtained even when the substrate was changed.
[0089] Next, the optical properties were measured for a conductive film prepared in the same manner as in Example 1, except that at least one of the seed layer material, the seed layer deposition conditions, and the seed layer thickness was changed from that in Example 1. The results are shown in Table 5.
[0090] [Table 5]
[0091] The total light relative reflectance characteristics in Table 5 were measured by the following method.
[0092] <Total light relative reflectance characteristics (low reflectance)> Using an ultraviolet-visible-near infrared spectrophotometer (UV-3600, manufactured by Shimadzu Corporation), the total light relative reflectance was measured when light was incident from the substrate side under the conditions of a halogen lamp as the light source, integrating sphere light reception including regular reflection (geometric condition d(8°:di), incident angle 8°), a barium sulfate reference plate, and a wavelength range of 300 to 800 nm, in accordance with JIS Z 8722 and CIE1976, and was evaluated according to the following evaluation criteria. In Table 1, R(%)@550nm indicates the total light relative reflectance at a wavelength of 550nm (the total light reflectance of the reference plate was taken as 100%). R(%)Max indicates the maximum total light relative reflectance at 300 to 800nm. When L* is 60 or less, it is possible to suppress the difference in visibility of reflected light between the wiring portion and the non-wiring portion when a patterned circuit board is produced using a light-transmitting substrate, which is preferable. (Evaluation Criteria) ⊚: L* was 50 or less. ○: L* was more than 50 and less than 60. ×: L* exceeded 60. n / a: Not measured
[0093] As shown in Table 5, the conductive films of Example 1 and Examples 13 to 17 of the present invention had excellent adhesion between the substrate and the seed layer, and excellent low reflectivity. Therefore, the conductive films of Example 1 and Examples 13 to 17 of the present invention are considered to be suitable as films for circuit boards, because they easily suppress the difference in visibility of reflected light between wiring and non-wiring when, for example, a patterned circuit board is produced using a light-transmitting substrate. In addition, among the conductive films of Comparative Examples 6 to 8 using "Ni-20Cr" (Cr (chromium) is 20 mass% and Ni (nickel) is 80 mass%) as the seed layer material, the conductive films of Comparative Examples 7 and 8 did not have a level of adhesion that could be used in practical use for circuit boards. The conductive film of Comparative Example 6 had a level of adhesion that could be used in practical use for circuit boards, but had an environmental problem in that Cr was used. [Explanation of symbols]
[0094] 1. Conductive film 2 Base material 3. Laminate 4 Seed layer 5 Thin copper layer 6 Film for circuit boards 7 Plated copper layer
Claims
1. A preparation step of preparing a substrate; A seed layer and a thin-film copper layer are formed on at least one surface of the base material in this order from the base material side. A laminate forming step of forming a laminate having the above structure, The laminate formation step includes forming the seed layer by a sputtering method. The process includes: The sputtering process uses a copper-nickel alloy target and is carried out without using an inert gas, using nitrogen (N 2 ) and oxygen (O 2 ) as an introduction gas, thereby forming the seed layer containing copper, nickel, nitrogen and oxygen; The nitrogen (N 2 ) Supply flow rate and oxygen (O 2 The ratio of the supply flow rate of the oxygen atom to the supply flow rate of the oxygen atom is 0.025≦(O 2 / N 2 )≦0.4 A method for producing a conductive film for circuit boards.
2. The conductive film for circuit boards according to claim 1 is manufactured by the method for producing the conductive film for circuit boards. obtaining a film; A plated copper layer is formed on the thin copper layer of the conductive film for circuit boards by electrolytic plating. and forming a film for circuit boards.
Citation Information
Patent Citations
Manufacture of 2-layer flexible substrate
JP1998256700A
Conductive substrate, and method for producing conductive substrate
JP2016122370A
Low reflection electrode for flat display or curved display
JP2017005233A
Laminate substrate, manufacturing method therefor, conductive substrate, and manufacturing method therefor
JP2017049723A
Substrate with conductive layers, substrate with touch-panel transparent electrodes, and method for fabricating same
WO2016140073A1